Characterization of differentially culturable bacteria in exenic culture and from tuberculosis patients - McIvor, Amanda (My University, 2018)
During tuberculosis (TB) disease, host-derived stresses and chemotherapy are thought to drive tubercle bacilli into differential growth states. This is evidenced by the presence of differentially culturable tubercle bacilli (DCTB) in the sputum of treatment naïve TB patients. These bacteria do not form colonies on solid media but can be cultured following supplementation of liquid media with culture filtrate as a source of growth stimulatory molecules. As DCTB are non-replicating and phenotypically drug tolerant, these organisms are thought to underpin the lengthy culture diagnosis and protracted treatment period required for TB disease. The purpose of this study was to investigate the use of culture filtrate in unmasking DCTB populations to: (1) quantify these populations in treatment naïve individuals, (2) assess the response of DCTB versus conventionally culturable bacteria to first-line treatment, (3) determine the relationship between DCTB cultured in the most probable number (MPN) assay with other TB culture methods and (4) to enhance currently employed culture diagnostic methods. The results from this study confirmed that treatment naïve individuals coinfected with HIV had significantly lower quanta of DCTB in their sputum compared to their HIV-negative counterparts. These findings implicate the host immune response in influencing the prevalence of DCTB in sputum. During treatment, four patterns of decline in DCTB were described. One quarter of the patient population accumulated DCTB during the first seven days of treatment, whilst approximately the same number of individuals displayed a rapid decline in DCTB during this period. The remaining individuals either displayed static or atypical patterns of DCTB over the first 14 days of treatment. Following treatment completion, residual DCTB was cultured in approximately two thirds of the patients analysed, suggesting that bacteriological sterilization of lungs was not achieved. These observations were confirmed using a novel fluorogenic probe specific for the detection of live Mycobacterium tuberculosis. DCTB cultured in the MPN assay was shown to directly correlate with current TB culture methods. These findings demonstrate a potential utility for the MPN assay in early bactericidal activity studies to assess the sterilising effect of new TB drugs on DCTB populations. Furthermore, the addition of culture filtrate to the BACTEC MGIT 960 assay reduced the rates of TB detection in smear-negative, HIV-positive individuals. Collectively, these observations demonstrate that the detection of DCTB in sputum can serve as a possible biomarker for treatment response. Further long term studies are required to determine if DCTB can use used to assess the risk of relapse disease and to test the efficacy of new drugs on persistent bacterial populations.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy Johannesburg, March 2018.